2013
DOI: 10.1371/journal.pone.0073327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IRS4 Levels on PI 3-Kinase Signalling

Abstract: Insulin receptor substrate 1 (IRS1) and IRS2 are well-characterized adapter proteins that relay signals from receptor tyrosine kinases to downstream components of signalling pathways. In contrast, the function of IRS4 is not well understood. IRS4 overexpression has been associated with acute lymphoblastic leukaemia and subungual exostosis, while point mutations of IRS4 have been found in melanomas. Here, we show that while IRS4 expression is low in most cancer cell lines, IRS4 mRNA and protein levels are marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 39 publications
0
29
1
Order By: Relevance
“…The IRS family is known to interact with many proteins, apart from the canonical p85 and GRB2, and can even form large multiprotein complexes (reviewed in refs 7, 50). Moreover, nuclear translocation with associated effects on, for example, DNA repair, rRNA synthesis and gene expression, has been reported for IRS proteins as well631515253, processes which also play a role in oncogenesis. Therefore, it may be useful to investigate these aspects in IRS4-induced tumours in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IRS family is known to interact with many proteins, apart from the canonical p85 and GRB2, and can even form large multiprotein complexes (reviewed in refs 7, 50). Moreover, nuclear translocation with associated effects on, for example, DNA repair, rRNA synthesis and gene expression, has been reported for IRS proteins as well631515253, processes which also play a role in oncogenesis. Therefore, it may be useful to investigate these aspects in IRS4-induced tumours in the future.…”
Section: Discussionmentioning
confidence: 99%
“…8a-c). Although PI3K/AKT pathway activation by IRS4 has been described before3132, the underlying mechanism thus far remained largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that overexpression of IRS4 induces higher levels of phosphatidylinositol 3,4,5-trisphosphate, Akt activation, and cell proliferation even in the absence of insulin or growth factors and that knockdown of IRS4 suppresses Akt activation and cell proliferation (21,22). We also showed that knockdown of IRS4 reduced the levels of P-Akt (Thr-308 and Ser-473) and P-GSK3␣/-3␤ and that expression of IRS4 restored the levels of these phosphoproteins in IRS4-depleted cells.…”
Section: Discussionmentioning
confidence: 99%
“…IRS1 and IRS2 are expressed ubiquitously in the entire body, and knock-out of IRS1 or IRS2 in mice leads to severe phenotypes, such as marked growth retardation and diabetes, respectively (26 -28). Conversely, IRS4 is expressed only in specific tissues, such as the thymus, pituitary gland, and hypothalamus (29 -31), and cell lines, such as 293T, 293AAV, and HepG2 cells (22,32). IRS4 knock-out mice exhibit mild defects in growth, reproduction, glucose homeostasis, and maternal behaviors (31,33).…”
Section: Discussionmentioning
confidence: 99%
“…The cells were cultured at 37°C and 5% CO2-humidified atmosphere in culture media. The cell lines have been previously used in a variety of studies, such as Hoxhaj et al, 2013, Randle et al, 2013and Rokstad et al, 2012 …”
Section: Human Net Cell Linesmentioning
confidence: 99%